Understanding Generation Y and their use of social media: a review and research agenda - Ruth N. Bolton; A. Parasuraman; Ankie Hoefnagels; Nanne Migchels; Sertan Kabadayi; Thorsten Gruber; Yuliya Komarova Loureiro; David Solnet (2013)
Understanding Generation Y and their use of social media: a review and research agenda